Studi Potensi Pengembangan Usaha Mikro Kecil dan Menengah (UMKM) Makanan Berbasis Roti Toast: Analisis Nilai Jual dan Makanan Praktis - Putri, Adinda Sutanto; Aulia Azizanuari; Ramadhani Salsabila A.; Safwanuzzaki Alfandi (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Study of the potential for developing Micro, Small and Medium Enterprises (MSMEs) in bread-based food "TOAST" which is a ready-to-eat food and sells well on the market. UMKM is a home business that sells modern food filled with ham, eggs, vegetables and other baked bread fillings. There are also sweet toasts filled with glaze. Don't forget the very practical presentation. The aim of this activity is to open and develop the "TOAST" shop and expand the culinary business. The results of the "TOAST" project show a positive response from local residents who are enthusiastic about visiting the Stand. The number of buyers also increased, which led to an increase in sales. It is hoped that the results of the "TOAST" business development project can be maintained and even improved. Marketing and promotion of the product itself will be carried out directly to the local community or via social media. The hope is that this food can be known more widely.